The Role of the National Unity and Political Agency of Surabaya City in Handling Demonstration Conflicts in Surabaya City - Dina Naimahtus Sholikah; Agus Widiyarta (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Demonstrations are one form of democratic expression frequently occurring in Surabaya, a hub for economic, social, and political activities in East Java. However, the dynamics of demonstrations often carry the potential for conflicts that may disrupt stability and public order. In this context, the Agency for National Unity and Politics of Surabaya City plays a strategic role as a mediator, facilitator, and conflict controller. This study aims to analyze the role of the Agency for National Unity and Politics of Surabaya City in managing conflicts during demonstrations through a descriptive qualitative approach. The results show that the Agency for National Unity and Politics of Surabaya City plays a crucial role in balancing respect for the public's right to express opinions and efforts to maintain social stability. Through an approach based on early detection and collaboration, the Agency for National Unity and Politics of Surabaya City can prevent and manage arising conflicts, although it still faces other challenges. Keywords: Agency for National Unity and Politics, Conflict Management, Demonstrations